HUBUNGAN KEPERCAYAAN DIRI DENGAN KEMAMPUAN BERADAPTASI PADA KARYAWAN DI PT. BUKAKA TEHNIK UTAMA BALIKPAPAN - Handoko, Tri Mei (MOTIVASI, 2013)
Confidence Relationships With Adaptive Capabilities: Studies on PT. Main Technical Bukaka Balikpapan Tri Mei Handoko. 08.11.1001.3510.029. Fakultas Psikologi Program Studi Psikologi. Universitas 17 Agustus 1945 Samarinda, 2013.Â This study aims to reveal the relationship of confidence with the ability to adapt Bukaka Technical Employees in Main Balikpapan PT. No matter how small changes in employee confidence will affect the employee's ability to adapt. Employee behavior will be correlated with the ability to adapt. The population in this study were employees working at PT. Main Technical Bukaka Balikpapan. As many as 143 samples taken from 319 respondents the existing population.Non-parametric correlation test using the product moment correlation coefficient to determine the relationship between variables X and Y values by comparing the count r with r table. From the calculations, r of 0.6250. After the results of the analysis are compared with the r table (table critical value) where N = 143 with a significance level of 0.05, it turns out empirical count r is greater than r table (0.6250> 0.176> 0.230). Thus the working hypothesis (hi) be accepted as true and reject the null hypothesis (ho). This means that there is a significant relationship between self-confidence with the adaptability of employees at PT. Main Technical Bukaka Balikpapan